An Ultrafast Optical Imaging System with Anamorphic Transformation Based on STEAM Structure - Guoqing Wang; Yuan Zhou; Rui Min; Fang Zhao; E Du; Xingquan Li; Cong Qiu; Dongrui Xiao; Chao Wang (Photonics)
The time-stretch (TS) imaging system is one type of ultrafast optical imaging system that enables imaging with an unprecedented imaging speed of tens of hundreds of megahertz. The TS imaging achieves linear one-to-one mapping between wavelength and time using a temporal dispersive medium. However, the data issue of high throughput and the fixed resolution in TS imaging limits its wide applications. In this paper, we propose an ultrafast optical imaging system with anamorphic transformation (AT) based on the STEAM structure, which has the benefit of data compression and changing group delay-related resolution. AT is obtained by the usage of chirped fiber Bragg grating (CFBG) with a nonlinear group delay profile. A state-of-the-art experimental demonstration shows that more acquired data are employed to describe the dense information region and the group delay-related resolution is improved by 58% using our proposed ultrafast optical imaging system without reducing the line scanning speed of 50 MHz. The proposal could increase the group delay-related resolution of the target image without adding extra data acquisition or changing the system setup, which has great potential in ultrafast optical imaging systems. Furthermore, the AT in our proposal could also be applied to data compression algorithms to mitigate the data issue in ultrafast optical imaging systems.